2014
DOI: 10.1515/text-2013-0035
|View full text |Cite
|
Sign up to set email alerts
|

Equivocation and doublespeak in far right-wing discourse: an analysis of Nick Griffin's performance on BBC's Question Time

Abstract: An analysis was conducted of the discourse of Nick Griin (leader of the BNP, the far right-wing British National Party), as featured on a television debate, broadcast on the popular BBC current afairs program Question Time (22 October 2009). On the basis of equivocation theory (Bavelas et al. 1990), it was hypothesized that Griin's discourse may be seen to relect an underlying communicative conlict. On the one hand, to be seen as racist is widely regarded as reprehensible in contemporary British society; on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…All users might, however, not be familiar with these and other similar expressions. The jargon then functions as a set of code words which pass over the heads of those who do not share the same far-right affiliations while being easily decoded by other far-right sympathizers (Åkerlund, 2021; Bhat & Klein, 2020; Bull & Simon-Vandenbergen, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…All users might, however, not be familiar with these and other similar expressions. The jargon then functions as a set of code words which pass over the heads of those who do not share the same far-right affiliations while being easily decoded by other far-right sympathizers (Åkerlund, 2021; Bhat & Klein, 2020; Bull & Simon-Vandenbergen, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Golding is being careful not to be self‐incriminating; he is being vague and avoiding saying how Britain First will take action as this has potentially negative consequences. Bull and Simon‐Vandenbergen () identified that the BNP portrayed vague messages with suggestions over its antiimmigration stance, a discursive strategy termed “calculated ambivalence” by Wodak (, p. 142).…”
Section: Discussionmentioning
confidence: 99%
“…It is a communicative strategy that a speaker might use to create a connection between two distinct things like concepts, ideas, views, events, etc. (Perelman & Olbrechts-Tyteca, 1969;Bull & Simon-Vandenberg, 2014). In reality, this connection is at the heart of the speaker's rhetoric while arguing to prove that a given conclusion is true.…”
Section: Association (Equivocation)mentioning
confidence: 99%
“…Moreover, the pragmatic perspective is explored to show how politicians use implicitness and explicitness to persuade their public and maintain control over them (Bull & Simon-Vandenberg, 2014).…”
Section: Introductionmentioning
confidence: 99%